(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to identify the impact of knowledge management on achieving competitive advantage and its success factors, and to present and highlight the difficulties and challenges facing the bank under study in applying the dimensions of knowledge management, and the extent to which the dimensions of knowledge management affect the achievement of competitive advantage in the bank under study. The researcher adopted the descriptive approach, which combined description and analysis of the data collected in the field from the sample of the study population. The researcher tested a simple random sample of administrative leaders and bank employees. In order to obtain the necessary data that serve and achieve the study’s objectives, she designed a questionnaire form to collect data related to the study variables. Statistical analysis methods were used using the Statistical Package for the Social Sciences (SPSS) program. The analysis included applying descriptive statistics measures such as frequencies, percentages, arithmetic mean, standard deviation, and t-tests. The study reached several conclusions, including the existence of a significant overall effect of all variables (organizational leadership, human resources, information technology) on the dependent variable (achieving competitive advantage), and partial acceptance of the main hypothesis, which states that there is a direct and statistically significant effect of knowledge management, through (information technology, organizational leadership), on achieving competitive advantage. The study recommended a set of recommendations, including: developing a clear strategic plan for knowledge management and its processes as an entry point for developing and improving banking performance and achieving competitive advantage; paying attention to knowledge management processes because they contribute to creating and developing cognitive capabilities and thus lead to obtaining competitive advantages; working to exploit the latest methods for developing electronic archiving systems for data and information; and searching for new products and innovating low-cost promotional methods in order to increase profits.